Development of a tool to measure patients’ satisfaction of hospital foodservice in a government hospital - Boughoula, Mariem; Jamaluddin, Rosita; Abd Manan, Nurul Aqmaliza; Abu Saad, Hazizi; Ab Karim, Muhammad Shahrim (Persatuan Pemakanan Malaysia, 2020)
Introduction: Dissatisfaction towards the quality of foodservice can affect several important aspects such as nutritional intake and financial burden. The effect of dissatisfaction towards nutritional aspect can be observed via a decline in dietary intake. Therefore, reliable and valid questionnaires are important to measure patients’ satisfaction with hospital foodservice. The main purpose of this study was to investigate the construct validity and reliability of a developed questionnaire in a local setting. Methods: A questionnaire adapted from previous studies and consisting of 27 statements from four dimensions, was administered to a total of 277 hospitalised patients in a government hospital. Factor analysis and reliability analysis were conducted using SPSS version 25. Results: Principal component of factor analysis revealed that the final questionnaire contained four main foodservice dimensions, namely food properties, staff and meal service reliability, customisation, and physical and social aspects. The reliability analysis revealed that the Cronbach’s alpha value ranged from 0.55 to 0.84 for these foodservice dimensions. The analysis showed that the alpha value differed from one dimension to another such as food properties (α=0.84), staff and meal service reliability (α=0.67), customisation (α=0.69) and physical and social aspects (α=0.55). Conclusion: Twenty-seven questionnaire items were retained because their factor loadings were greater than 0.35. Therefore, the questionnaire on patients’ satisfaction towards hospital foodservice was considered reliable and valid. The classification of the four dimensions provided detailed information of the satisfaction level, relationship and influence on the foodservice dimensions, which contributed to satisfaction towards hospital foodservice.